A Psoriatic Patient-Based Survey on the Understanding of the Use of Vaccines While on Biologics During the COVID-19 Pandemic. Issue 3 (May 2021) - Le, Heather; Vender, Ronald B.
Background: Psoriatic patients who are actively receiving biologic treatment have protocols in place to achieve optimal immunity. Inactivated vaccines are safe to use during biological treatment, without interruption. Conversely, live vaccines are used with caution and likely interruption of treatment. Given the novel coronavirus (SARS-CoV-2), nation-wide administration of vaccinations is underway. Objective: This survey gathered information on the level of education psoriatic patients have concerning vaccinations. Methods: An electronic survey was sent to 661 patients suffering from psoriasis. Patients originated from a single solo-practitioner community-based dermatology practice. Results: The average percentage of patients who understand the difference between live and inactivated vaccines between the control and study group was 36.6%. The average response to not knowing the difference between the vaccines was 36.6% and 26.6% were "unsure." When asked if it was possible to receive inactivated vaccines while on a biologic, the mass response amidst the control and study group was "unsure" (66.9%). Conclusion: This questionnaire demonstrates that there is a need for supplementary education about vaccines for psoriatic patients on a biologic. Physicians will need to counsel their patients on the use of potential vaccines for SARS-Cov2 while on biologics.